Development Of Hydraulic Launch Assist Testbench - Ramli, Muhammad Faiz (Universiti Sains Malaysia, 2019)
The hydraulic hybrid systems are design to reduce the fuel consumption of vehicle in automotive industry. The secondary power source for hydraulic hybrid systems are hydraulic component that is connected to energy storage. The energy use back to assist the vehicle during acceleration by hydraulic motor. The focus of the research is to design a suitable configuration for the Perodua Myvi to be modified to become a hydraulic hybrid vehicle. The configuration that is plan to be installed on the rear wheel to avoid complexity since Perodua Myvi is frontwheel-drive the rear wheels are spin freely. Due to that, the hydraulic acceleration boost system is implement onto the rear axle of Perodua Myvi. The performance of the hydraulic component is measured and compared to the drive cycle by World Harmonised Light Vehicle Test Procedure, (WLTP). The percentage different for the maximum acceleration from the result and drive cycle is 65.412 %. For the average acceleration from the result and drive cycle is 38.412%.The energy recovery during the hydraulic acceleration boost is also being measured. The energy that are able to recover is in the range 23% to 29 %.